Chapparvovirus DNA Found in 4% of Dogs with Diarrhea - Fahsbender, Elizabeth (Viruses, 2019)
Feces from dogs in an unexplained outbreak of diarrhea were analyzed by viral metagenomics revealing the genome of a novel parvovirus. The parvovirus was named cachavirus and was classified within the proposed Chapparvovirus genus. Using PCR, cachavirus DNA was detected in two of nine tested dogs from that outbreak. In order to begin to elucidate the clinical impact of this virus, 2,053 canine fecal samples were screened using real-time PCR. Stool samples from 203 healthy dogs were positive for cachavirus DNA at a rate of 1.47%, while 802 diarrhea samples collected in 2017 and 964 samples collected in 2018 were positive at rates of 4.0% and 4.66% frequencies, respectively (healthy versus 2017-2018 combined diarrhea p-value of 0.05). None of 83 bloody diarrhea samples tested positive. Viral loads were generally low with average real-time PCR Ct values of 36 in all three positive groups. The species tropism and pathogenicity of cachavirus, the first chapparvovirus reported in feces of a placental carnivore, remains to be fully determined.